The Boys from Brazil - Ira Levin (UK Pan Books, 1977)
"'Let's get down to business now, boys.' Tipping his cropped gray head, he lowered his glasses and looked at the men. They faced him attentively, cigars poised. Silence took the room. 'You know what you're going to do,' the man in white said. 'Ninety-four men have to die on or near certain dates in the next two and a half years....Their deaths are the final step in an operation to which I and the leaders of the Organization have devoted many years....The hope and the destiny of the Aryan race lie in the balance.'" Thus opens Ira Levin's masterful novel. Why have these harmless aging men been marked for murder? What is the hidden link that binds them? What interest can they possibly hold for their killers: six former SS men dispatched from South America by the most wanted Nazi still alive, the notorious "Angel of Death"? One man alone must answer these questions and stop the killings--Nazi-hunter Yakov Liebermann
Keywords: Literature (3GdCOHs; General -- Fiction; Nazi hunters; Murder -- Fiction; Organized crime -- Fiction; Science fiction